Comparing Farm Biosecurity and Antimicrobial Use in High-Antimicrobial-Consuming Broiler and Pig Farms in the Belgian–Dutch Border Region - Caekebeke, Nele; Jonquiere, Franca J.; Ringenier, Moniek; Tobias, Tijs J.; Postma, Merel; van den Hoogen, Angelique; Houben, Manon A. M.; Velkers, Francisca C.; Sleeckx, Nathalie; Stegeman, J. Arjan; Dewulf, Jeroen (Frontiers in Veterinary Science, 2020)
As antimicrobial resistance is a worldwide problem, threatening both livestock and public health, understanding the drivers for resistance in different settings and countries is essential. Therefore, thirty pig and thirty poultry farms with country-specific high antimicrobial use (AMU) were recruited in the Belgian-Dutch border region. Information regarding production parameters, farm characteristics, biosecurity and AMU was collected. On average, more biosecurity measures were implemented on Dutch farms, compared to Belgian farms in both animal species. In addition, more opportunities were found to increase the level of internal biosecurity compared to external biosecurity in both countries. Antimicrobial use, quantified as treatment incidence (TI), differed marginally significant between broiler farms in Belgium and the Netherlands (median BE: 8; NL: 3), whereas in weaned piglets (median BE: 45; NL: 14) and finishing pigs (median BE: 5; NL: 1) there was a substantial difference in AMU between farms from both countries. Overall, Dutch farms showed less between-farm variation in TI than Belgian farms. In both poultry and pig production, the majority of antimicrobials used were extended-spectrum penicillins (BE: 32% and 40%; NL: 40% and 24% for poultry and pigs respectively). Compared to Belgian farms, Dutch poultry farms used high amounts of (fluoro)quinolones (1% and 15% of total AMU respectively). None of the production parameters between broiler farms differed significantly but in pig production, weaning age in Belgian farms (median: 23) was lower than in Dutch farms (median: 27). These results indicate considerable room for improvement in both countries and animal species. Farm-specific preventive strategies can contribute to lowering the risk for animal disease, and hence the need for AMU.